The Professional Development of Foreign Language Teacher Educators: Another Challenge for Professional Communities - González Moncada, Adriana; Sierra Ospina, Nelly (Íkala, Revista de Lenguaje y Cultura, 2005)
The professional development of Colombian foreign language teacher educators faces many challenges that require individual and institutional actions as well as the participation of a community of teacher educators. This paper reports the findings of a qualitative study in which eighteen Colombian teacher educators describe their professional alternatives to achieve higher standards in their jobs. Data collection includes focus groups, in-depth interviews, a questionnaire, and e-mail correspondence. The analysis showed that teaching advanced courses, doing research, attending and presenting in international conferences, being involved in reflective practice, developing autonomous agendas, and networking represent the best means to accomplish their professional growth. Received: 30-04-05 / Accepted: 11-08-05 How to reference this article: González Moncada, A. (2005). The Professional Development of Foreign Language Teacher Educators: Another Challenge for Professional Communities. Íkala. 10(1), pp. 11 – 39.